Comparison between sports drink and coconut water on cardiovascular endurance performance among football players / Siti Soraya Mohd Elias, Muhammad Alif Zulkifli and Noor Fatihah Ilias - Mohd Elias, Siti Soraya; Zulkifli, Muhammad Alif; Ilias, Noor Fatihah (Universiti Teknologi MARA, 2023)
A sports drink is a drink containing electrolytes and glucose, meanwhile coconut drink is known as a natural source of sports drink. Both drinks have the benefit of restoring energy and electrolyte, especially when ingested during strenuous physical activity that requires maximum endurance performance. The purpose of this study was to compare the effects of sports drinks and coconut drinks in enhancing cardiovascular endurance performance among UiTM football players. A total of 24 male participants representing Universiti Teknologi MARA Football Club (UiTM FC) were recruited. Participants were randomly assigned into three groups that are isotonic drink group (IDG) (n=8), the coconut drink group (CDG) (n=8), and the control group (n=8). Cardiovascular endurance performance was determined based on bleep test results at the pre-test and post-test. The intervention was conducted by giving a different type of drink according to the assigned group. IDG received 100 plus isotonic drink, CDG received a Vita Coco drink and CG were only given plain water. After the end of the pre-test session, the participants were given 2-hour to rest, and drinks were given according to their group. After 2-hour of rest, the participants continue with the post-test. The level of VO2 max was measured by an equation based on the bleep test results. The result shows there was a significant increment in pre-post-test VO2 max level within all groups, showing improvement in the mean level of VO2 max at post-test. The mean of pre-post-test VO2 max for the three respective groups was IDG 47.53 ± 6.32 to 49.46 ± 5.88 ml/kg/min, CDG 47.01 ± 3.45 to 48.81 ± 3.29 ml/kg/min and CG 47.06 ± 3.11 to 47.91 ± 3.43 ml/kg/min. However, there was no significant difference (p=0.276) between groups and pre-post-test VO2 max level. Looking at between groups effect, there was no significant effect (p=0.900) between these three groups and their VO2 max level. In conclusion, there was a significant positive change in the participant's pre-post-test VO2 max level for all three groups across two different periods at the pre-test and post-test. This suggests ingesting drinks between exercises substantially improved football players' cardiovascular endurance performance. However, there was no significant difference in the participants' cardiovascular endurance performance between the three groups. This indicates the type of drink does not influence the cardiovascular endurance performance among these football players.